2015
DOI: 10.1007/s12664-015-0563-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of celiac disease and its dietary manipulation on children and their caregivers

Abstract: Noncompliance to gluten-free diet was noted in 24 % of children with celiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 26 publications
1
37
1
3
Order By: Relevance
“…Two cross-sectional studies and one case-control article were rated as "Poor." This rating was tied to the following assessments: Khurana et al 8 lacked information regarding population details and Roma et al 9 and Ljungman and Myrdal 10 did not discriminate the factors affecting compliance, namely those that were evaluated as a dichotomic variable when more discrimination was possible.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Two cross-sectional studies and one case-control article were rated as "Poor." This rating was tied to the following assessments: Khurana et al 8 lacked information regarding population details and Roma et al 9 and Ljungman and Myrdal 10 did not discriminate the factors affecting compliance, namely those that were evaluated as a dichotomic variable when more discrimination was possible.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…In our review, eight articles evaluated maternal education. Four articles (two of "Good" quality 11,13 and two of "Medium" 5,17 quality) showed maternal education to be a significant factor for compliance to a GFD while another four (two of "Good" quality 16,18 and two of "Poor" quality 8,9 ) failed to show an effect.…”
Section: Maternal Educationmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies demonstrated the importance of caregivers in assisting in the social and psychological drama of a chronic condition and in supporting a faster recovery and higher compliance to treatment. With regard to CD, only a few studies adopted the caregivers' perspective, mainly drawing the attention to their effect on patients' quality of life and treatment adherence (21). In the clinical practice, caregivers' well-being is not routinely assessed (22).…”
Section: Discussionmentioning
confidence: 99%
“…This is so since the poorer population do not attend a doctor very often and even when the diagnosis is established, there is a greater possibility of non-adherence to a gluten-free diet due to their unfavourable financial situation for purchasing gluten-free products (18 (Table 8). Only a trace of gluten in food is sufficient to produce damage to the mucosa of the small intestine and subsequent complications (23)(24)(25). The lack of awareness of the necessity of strict adherence to a gluten-free diet in children and adolescents can cause serious problems in the further course of the disease.…”
Section: Discussionmentioning
confidence: 99%